2017
DOI: 10.1111/wvn.12243
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Physiopsychosocial Factors and Spiritual Well‐Being in Elderly Residents: Implications for Evidence‐Based Practice

Abstract: The findings address the fact that the practice of spirituality is multidimensional and multileveled. Psychosocial interventions for institutionalized elders with disabilities should focus on increasing nurse-patient interaction and providing access to meaningful social activities to improve mental health and spiritual well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…Some studies have shown that the Quality of Life score among elderly women was lower than that of men at the same age and have related it to longer life span, more illnesses, lower educational level and income, lack of autonomy, and more social and cultural limitations imposed on women (Mangen et al 2017). The mean score of life quality among the elderlies in Belo Horizonte City in Brazil and in Taiwan was 52.57 and 58.3, respectively (Miranda, Soares & Silva 2016;Chen & Chen 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the Quality of Life score among elderly women was lower than that of men at the same age and have related it to longer life span, more illnesses, lower educational level and income, lack of autonomy, and more social and cultural limitations imposed on women (Mangen et al 2017). The mean score of life quality among the elderlies in Belo Horizonte City in Brazil and in Taiwan was 52.57 and 58.3, respectively (Miranda, Soares & Silva 2016;Chen & Chen 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Chen et al, 2017; Erichsen & Bussing, 2013) Only variables with < 10% missing data values were considered.…”
Section: Methodsmentioning
confidence: 99%
“…Spirituality and religiosity are a resource used for several patients to cope with chronical disease which have a positive impact on their quality of life and well-being [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of spirituality is extremely general and multidimensional [7,10,11] anchored in subjective reasons and influenced by each person's life experiences, and includes a set of beliefs, that are not associated with religious doctrines [4] in order to disclose a meaning and understanding life search and trust in a transcendent source, in nature or others, with God or a higher power [7,8]. In religious people, spirituality may reflect the religious doctrine, creeds and philosophical beliefs being the life and disease understands in those perspective [12,13].…”
Section: Introductionmentioning
confidence: 99%